Seminal exosomes induce interleukin-6 and interleukin-8 secretion by human endometrial stromal cells. (April 2019) - Paktinat, Shahrokh; Hashemi, Seyed Mahmoud; Ghaffari Novin, Marefat; Mohammadi-Yeganeh, Samira; Salehpour, Saghar; Karamian, Amin; Nazarian, Hamid
Abstract: Objective: Exosomes are extracellular microvesicles that participate in intercellular communication. Seminal plasma (SP) contains very large amounts of exosomes which are deposited in female genital tract after insemination. Although the response of vaginal cells to seminal exosomes (SE) is recently being elucidated, the interaction of uterine cells with SE is still unknown. Here, we aimed to evaluate the effect of SE on cytokine secretion by human endometrial stromal cells (eSC). Study design: Exosomes were isolated from the semen samples of healthy men with proven fertility and characterized using common exosome characterization methods. Human eSC were isolated from endometrial biopsies obtained from healthy premenopausal women. For exosome internalization analysis, SE were labeled with PKH67 green fluorescent dye and incubated with the cells. For investigating the effect of SE on cytokine secretion of eSC, we measured levels of interleukin (IL)-6, IL-8, IL-10, IL-1α, and leukemia inhibitory factor (LIF) in the culture supernatants of control and experimental groups by enzyme-linked immunosorbent assay (ELISA) after 24 h of incubation. Results: Our results demonstrated that SE are internalized by eSC and subsequently induce them to produce IL-6 and IL-8, the cytokines which are involved in the immunology of embryo implantation. Conclusion: The findings of the present study suggest that SE contribute to the immunoregulatory functions of SP in the uterus and may participate in embryo implantation process. Therefore dysfunction of intracellular machineries of SE biogenesis and secretion, inadequate production, defective transportation to the uterus and impaired communication with endometrium may play a distinct role in pathophysiology of embryo implantation failure.